2019
DOI: 10.1186/s12986-019-0379-y
|View full text |Cite
|
Sign up to set email alerts
|

High serum uric acid level is a mortality risk factor in peritoneal dialysis patients: a retrospective cohort study

Abstract: Background The results remain controversial with regards to the impact of serum uric acid on clinical outcomes from peritoneal dialysis population. The aim of our study was to investigate the influence of serum uric acid levels on mortality in peritoneal dialysis patients. Methods Data on 9405 peritoneal dialysis patients from the Zhejiang Renal Data system were retrospectively analyzed. All demographic and laboratory data were recorded at baseline. The study cohort was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Among them, in a retrospective study including 156 PD patients, Feng et al [44] reported that higher SUA levels were associated with increased all-cause mortality. Xia et al [12] reported that elevated SUA level was an independent risk factor for all-cause and CVD mortality in male PD patients [45] and CVD mortality in diabetic male PD patients [46] in a retrospective cohort study of 985 PD patients and 328 PD patients with diabetes, respectively. And, a study from Xiang et al [12] showed that high SUA level was associated with higher all-cause but not CVD mortality, and the prognostic effects were more prominent in male, hypoalbuminemia, lower BMI, and nondiabetes patients subgroup [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, in a retrospective study including 156 PD patients, Feng et al [44] reported that higher SUA levels were associated with increased all-cause mortality. Xia et al [12] reported that elevated SUA level was an independent risk factor for all-cause and CVD mortality in male PD patients [45] and CVD mortality in diabetic male PD patients [46] in a retrospective cohort study of 985 PD patients and 328 PD patients with diabetes, respectively. And, a study from Xiang et al [12] showed that high SUA level was associated with higher all-cause but not CVD mortality, and the prognostic effects were more prominent in male, hypoalbuminemia, lower BMI, and nondiabetes patients subgroup [12].…”
Section: Discussionmentioning
confidence: 99%
“…As a common feature of protein-energy wasting [9], lower appendicular skeletal muscle mass (ASM) was shown to independently predict mortality in PD patients [10,11]. The gender and diabetics status were revealed to modify the prognostic effect, and the study by Xiang et al [12] suggested that the adverse effect of higher SUA level on all-cause mortality was also more prominent in hypoalbuminemia and normal-weight groups of PD patients. However, the relationship between SUA and ASM was unknown in PD population and the effect of the ASM level on the association between SUA and all-cause or CVD mortality in PD patients remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients receiving peritoneal dialysis (PD), the relationship between serum UA level and mortality appears variable. Although many reports have demonstrated a positive relationship, 18 21 some reports have described an inverse, 22 a U-shaped, 23 or no relationship 24 between UA levels and all-cause or CV mortality rate. Potential reasons for these discrepancies were diversities in methods of analysis, patient characteristics, dialysis prescription, and confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…In the general population, some studies [7-9], but not all [10-12], have indicated that an elevated SUA level is a risk factor for the CVD and all-cause mortality. In the peritoneal dialysis (PD) patients, studies have shown positive [13-15], negative [16] or U-shaped [17] associations between SUA and mortality. To date, only a handful of studies have detected the association between SUA levels and the risk of mortality in maintenance hemodialysis (MHD) patients and reached inconsistent conclusions.…”
Section: Introductionmentioning
confidence: 99%